2018
DOI: 10.1007/978-3-030-00126-1_20
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Acoustic Evidence of Nasalization as a Compensatory Mechanism for Voicing in Spanish Apraxic Speech

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
1
2
0
1
Order By: Relevance
“…Our preliminary results indicate that only participants with AoS insert vocalic elements in unvoiced clusters and that some of these insertions are only detected with acoustic analyses (are not perceived by the human ear). This result is in line with the literature showing specific acoustic features in AoS (Marczyk et al, 2019), and here we show that they differentiate AoS from 4 other groups of participants with different motor speech disorders. The observed vocalic insertions can have two different interpretations: (1) some patients may insert vowel elements into unvoiced clusters in order to facilitate the articulation of the two successive consonantal elements.…”
Section: Discussionsupporting
confidence: 93%
“…Our preliminary results indicate that only participants with AoS insert vocalic elements in unvoiced clusters and that some of these insertions are only detected with acoustic analyses (are not perceived by the human ear). This result is in line with the literature showing specific acoustic features in AoS (Marczyk et al, 2019), and here we show that they differentiate AoS from 4 other groups of participants with different motor speech disorders. The observed vocalic insertions can have two different interpretations: (1) some patients may insert vowel elements into unvoiced clusters in order to facilitate the articulation of the two successive consonantal elements.…”
Section: Discussionsupporting
confidence: 93%
“…First, some patients may insert vocalic elements into unvoiced clusters in order to facilitate the articulation of the two successive consonantal elements. This could be seen as a compensatory mechanism, as hypothesized by Marczyk et al (2018). These authors reported that participants with AoS produced anticipated voicing for the consonants/b, d, g/only in one-third of the cases and that this portion was strongly related to a longer nasal murmur.…”
Section: Vocoid Epenthesis In Aosmentioning
confidence: 81%
“…Given this limitation, acoustic analyses have been applied to better characterize and quantify vocoid epenthesis in neurotypical speakers (see Bürki et al, 2011 ; Ridouane & Fougeron, 2011 ). To our knowledge, vocoid epenthesis has not been analyzed acoustically in motor speech disorders, although acoustic analyses have been conducted on other acoustic parameters such as voice (see Kent & Kim, 2003 for a review), speech rate (Kent et al, 2000 ; Wang, 2002 ), rhythm (Stuntebeck, 2002 ), vowel and syllable duration (Blumstein et al, 1980 ; Laganaro et al, 2012 ), and voice onset time – VOT – (Auzou et al, 2000 ; Blumstein et al, 1980 ; Marczyk et al, 2018 ; Melle & Gallego, 2012 ; Ouden et al, 2018 ), formant frequencies (K. L. Haley et al, 2001 ; Ouden et al, 2018 ) and in coarticulation (Tjaden, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…banque). Les résultats de cette recherche(Marczyk et al, 2017(Marczyk et al, , 2018a(Marczyk et al, , 2018b pourraient constituer un point de départ pour une rééducation orthophonique ciblant le contraste de voisement. Ainsi, les mécanismes compensatoires mis en évidence ici sont étroitement dépendants de paramètres linguistiques, dans la mesure où les locuteurs apraxiques ne développent pas de stratégie compensatoire propre, mais renforcent un mécanisme d'ajustement moteur aussi utilisé par les locuteurs sains de cette langue dans un contexte difficile pour la réalisation du voisement.La dysarthrie regroupe un ensemble de maladies dont la caractéristique commune est une atteinte du système nerveux central ou périphérique dégradant la transmission des messages neuraux vers les muscles sollicités dans la production de la parole(Darley et al, 1975).…”
unclassified